Relaxation Rate and Mobility of a Two-dimensional Electron Gas in MgZnO/ZnO Heterostructures Including Exchange and Correlation Effects - Tai, Vo Van; Khanh, Nguyen Quoc (Communications in Physics, 2017)
We investigate the relaxation rate and mobility of a two-dimensional electron gas (2DEG) confined in MgZnO/ZnO heterostructures (HSs) for temperatures , taking into account exchange and correlation effects. We use the variational-subband-wave-function model for carrier confinement and assume that the electrons are confined to the lowest subband and scattered by acoustic phonons via deformation potential (DP) and piezoelectric (PE) fields, polar LO phonons, interface roughness (IRS), interface charges (IFCs) and the background impurities (BIs). The calculations are based on the linearized Boltzmann equation (BE) and the relaxation time approximation, assuming the scattering by acoustic phonons to be quasi-elastic. We consider three physically distinct temperature ranges with respect to phonon scattering: the Bloch-Grüneisen (BG), equipartition (EP), and inelastic regimes. In the inelastic regime at high temperatures, where the scattering from polar LO phonons becomes important, we solve directly the linearized BE by an iterative method and compare the obtained results with those of the low-temperature and high-energy relaxation-time approximation. Our calculated low-temperature mobility is in good agreement with the recent experiment